Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1530/eje.0.1320735
|View full text |Cite
|
Sign up to set email alerts
|

δ-Iodolactones decrease epidermal growth factor-induced proliferation and inositol-1,4,5-trisphosphate generation in porcine thyroid follicles—a possible mechanism of growth inhibition by iodide

Abstract: delta-Iodolactone (6-iodo-8,11,14-eicosatrienoic delta-lactone, delta-IL), an iodinated derivative of arachidonic acid, has been shown to be synthesized in thyroid tissue and to inhibit thyroid cell proliferation. It is discussed as a potential mediator of the autoregulatory pathway of iodide in cyclic adenosine-3',5'-monophosphate (cAMP)- and thyrotropin (TSH)-independent growth. We therefore further localized the action of iodide and of delta-IL in isolated porcine thyroid follicles. Epidermal growth factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
(30 reference statements)
1
17
2
3
Order By: Relevance
“…The iodolactone growth inhibitory mechanism, which is decreased in iodine-deficient thyroid cells, is believed to occur via inhibition of the specific EGFdependent production of IP3, a signal transducer that modulates thyroid cell proliferation (43). However, this compound had no effect on TSH-mediated cAMP formation in porcine follicles (43).…”
Section: Increased Thyroid Cell Responsiveness To Tshmentioning
confidence: 99%
See 1 more Smart Citation
“…The iodolactone growth inhibitory mechanism, which is decreased in iodine-deficient thyroid cells, is believed to occur via inhibition of the specific EGFdependent production of IP3, a signal transducer that modulates thyroid cell proliferation (43). However, this compound had no effect on TSH-mediated cAMP formation in porcine follicles (43).…”
Section: Increased Thyroid Cell Responsiveness To Tshmentioning
confidence: 99%
“…However, this compound had no effect on TSH-mediated cAMP formation in porcine follicles (43). Considered to be a more likely candidate is 2-iodohexadecanal (44), a major iodolipid formed in horse thyroid when incubated with iodide (45), but which is also detectable in the thyroid of other species, including humans and rats.…”
Section: Increased Thyroid Cell Responsiveness To Tshmentioning
confidence: 99%
“…Among these, 6-iodo-5-hydroxy-8,11,14-eicosatrienoic acid δ-lactone (IL δ) and 2-iodohexadecanal (2-IHDA) have been shown to inhibit several thyroid parameters and its participation in thyroid autoregulation has been suggested (Panneels et al, 2009). Moreover it was demonstrated that IL δ prevents goiter growth in rats (Pisarev et al, 1988 and that, in vitro, it inhibits thyroid cell proliferation in pigs (Dugrillon and Gärtner, 1995;Dugrillon et al, 1990), humans (Dugrillon et al, 1994) and FRTL-5 cells (Pisarev et al, 1992). Regarding 2-IHDA, in in vitro studies no growth suppressing effect could be demonstrated by measuring thymidine incorporation in primary cultures of dog thyroid cells (Panneels et al, 1994a) but we have demonstrated that it has an antigoitrogenic action (Thomasz et al, 2010a).…”
Section: Introductionmentioning
confidence: 70%
“…Addition of the aldehyde 2-iodohexadecanal (2-IHDA) to thyroid slices and membranes reproduces two known XItype effects of iodide: the inhibition of adenylyl cyclase (Panneels et al, 1994b) and the inhibition of H 2 O 2 generation (Ohayon et al, 1994;Panneels et al, 1994a). Iodolactone at high concentrations inhibits the proliferation of porcine thyroid cells induced by EGF (Dugrillon and Gartner, 1995).…”
Section: Candidates XImentioning
confidence: 99%